Hubungan Antara Pemberian Reward Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran PKN SDN Talang Leban - Julia Sawitri; Ramanata Disurya; Tanzimah Tanzimah (Departement of Mathematics Education, 2023)
Abstract This study aims to determine whether there is a relationship between giving rewards on student learning outcomes in Civics subjects at SDN TalangLeban. This type of research is quantitative research with correlation using techniques sampling total to get class III, totaling 15 students as the research sample. This data collection technique uses questionnaires and tests. The results showed a significant value between the questionnaires reward and test about learning outcomes with the results of the correlation test rxy= 0.876 > 0.5140, the coefficient of determination is 75%, meaning that the donation reward on learning outcomes has a